(untitled) (Research, Society and Development, 2022)
Objective: analyze the effects based on herbal medicine on dyslipidemia treatment. Methodology: this literature review is on English, Portuguese, and Spanish used searches between 2017 and 2021 available on databases PubMed, Scielo, and Google Scholar. The research was limited to human beings, according to its evidence level. Results: the studies point to the Allium sativum L. (garlic) effectiveness use to reduces total cholesterol (TC), low-density lipoprotein (LDL-c) in addition to reducing antithrombotic action and platelet aggregation. The Linum usitatissimun L. (linseed), in seed shape of powder, biscuit, and oil, shows those benefits on reductions level of TC, LDL-c, high-density lipoprotein (HDL-c), and triglycerides (TG) due to its fiber omega-3 content. The Avena sativa (oat) also shows positive results on reduction levels TG, LDL-c, and non-HDL-c because of its high content of beta-glucan-type fibers. Conclusion: the herbal medicines analyzed presented great results from reduction and dyslipidemia control due to their balance on circulating lipids.